A Study of Talent Management Practices and Strategies in the Service Sector - Shweta Bobhate (International Journal of Engineering and Management Research, 2020)
Talent management is a mechanism which involves hiring, assigning, transferring, growth and retaining of employees in the organisation. It is important because it ensures top talent is attracted and effective employee performance, employee’s engagement and retainment of top talent. A thorough review of the work carried out shows that businesses are experiencing a talent shortage in this competitive period, which has placed pressure on them to recruit the best talent and to ensure that workers enter the company and choose to remain in the organization rather than seeking opportunities elsewhere. The importance of the different components of talent management for employees was another unexplored area. Existing research has not been able to resolve the problem of defining the importance of the different talent management elements and the weighting they bear for employees. The problem of employee perception and management perception of the efficacy of talent management activities has also not been discussed, to address this gap the researcher has attempted to study talent management practices in service sector. The author followed a systematic approach to address the research questions, the literature was reviewed, in research methodology, primary data was collected through questionnaire which followed a sampling method accompanied by hypothesis testing which revealed that the effective practices boosts up the efficiency of the employees and performance of the organization too.